2021
DOI: 10.1080/02619768.2021.1900112
|View full text |Cite
|
Sign up to set email alerts
|

Case-based teacher education preparing for diagnostic judgement

Abstract: An integrated part of teaching is to face unexpected situations. Teachers have to make immediate decisions, and these decisions may have a great impact on many people. An important question is how teacher education can prepare students for unexpected situations. The aim of this practitioner research study is to investigate if case-based teaching can contribute to reducing the perceived gap in teacher education. A step-wise model was introduced for the students and data based on the student teachers' experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Precisely for this reason, this method has the potential to be effective in helping preservice teachers become professional decision-makers. Helleve et. al.…”
Section: Discussion Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precisely for this reason, this method has the potential to be effective in helping preservice teachers become professional decision-makers. Helleve et. al.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…The principal reason for this is that the environment in which the teaching-learning process takes place is unstructured and dynamic (Leinhardt & Greeno, 1986). In the unpredictable situations that occur in this dynamic environment, teachers make hundreds of nontrivial decisions every day (Helleve et. al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Various formats and approaches to case composition have been employed to support pre-service and in-service teacher learning, with cases composed by teachers, researchers and teachers and researchers together (Alpert & Bechar, 2007;Day & Loughran, 2007;Dorner et al, 2017;Helleve et al, 2023;Oliver et al, 2018;Ulvik et al, 2022). Studies such as those by Anders et al (2017) and Richards et al (2015) have identified benefits for preservice teachers arising from authoring cases of their experiences, which included opportunities for critical reflection on the realities of classroom life.…”
Section: Teacher Cases Of Practice In Educational Researchmentioning
confidence: 99%
“…Various formats and approaches to case composition have been employed to support pre‐service and in‐service teacher learning, with cases composed by teachers, researchers and teachers and researchers together (Alpert & Bechar, 2007; Day & Loughran, 2007; Dorner et al., 2017; Helleve et al., 2023; Oliver et al., 2018; Ulvik et al., 2022). Studies such as those by Anders et al.…”
Section: Impetus and Approaches For The Mobilisation And Disseminatio...mentioning
confidence: 99%
“…Case-based learning is an effective educational strategy, used in a variety of fields, including teacher education. [2] Case studies offer the opportunity for learners to explore situations that mimic real life, in the safe setting of the classroom. Learners can develop critical thinking skills as they grapple with ill-defined and nuanced situations presented in the case.…”
Section: Introductionmentioning
confidence: 99%